2021
DOI: 10.3390/biomedicines10010021
|View full text |Cite
|
Sign up to set email alerts
|

miR-671-5p Inhibition by MSI1 Promotes Glioblastoma Tumorigenesis via Radioresistance, Tumor Motility and Cancer Stem-like Cell Properties

Abstract: MicroRNAs (miRNAs) could be potential biomarkers for glioblastoma multiforme (GBM) prognosis and response to therapeutic agents. We previously demonstrated that the cancer stem cell marker Musashi-1 (MSI1) is an RNA binding protein that promotes radioresistance by increasing downstream RNA stability. To identify that MSI1 interacts with miRNAs and attenuates their function, we also get candidate miRNAs from the mRNA seq by predicting with TargetScan software. miR-671-5p in GBM cells interacts with MSI1 by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…MSI1 causes tumor migration by binding with ICAM1 RNA, leading to poor prognosis [ 24 ]. MSI1 can be inhibited by microRNAs to reduce brain carcinogenesis [ 25 ]. RBFOX1 could not be confirmed based on previous studies to have positive or negative correlations with gliomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…MSI1 causes tumor migration by binding with ICAM1 RNA, leading to poor prognosis [ 24 ]. MSI1 can be inhibited by microRNAs to reduce brain carcinogenesis [ 25 ]. RBFOX1 could not be confirmed based on previous studies to have positive or negative correlations with gliomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of glucose metabolism by PKM2 can reinforce the antioxidant defense system in the development of radio-resistance in GBM [ 145 ]. miRNA-671–5p undergoes down-regulation by MSI1 in GBM and it can mediate CSC features and metastasis of tumor cells [ 146 ]. Noteworthy, miRNA-671–5p down-regulation results in activation of STAT3 and TRAF2 as two downstream targets to mediate radio-resistance in GBM cells [ 146 ].…”
Section: Lncrnas In Therapy Responsementioning
confidence: 99%
“…miRNA-671–5p undergoes down-regulation by MSI1 in GBM and it can mediate CSC features and metastasis of tumor cells [ 146 ]. Noteworthy, miRNA-671–5p down-regulation results in activation of STAT3 and TRAF2 as two downstream targets to mediate radio-resistance in GBM cells [ 146 ]. The nuclear translocation of Rad51 can mediate radio-resistance in GBM cells.…”
Section: Lncrnas In Therapy Responsementioning
confidence: 99%
“…RBP can regulate the modification and translation of mRNA and affect the processing of miRNA and circRNA, playing a key role in cancer progression and metastasis [114]. Musashi-1 (MSI1), as a RBP and a CSC biomarker, can increase downstream RNA stability and interact with miRNA, thereby altering the expression and activity of OCT4 and STAT3 [115,116]. Studies have shown that RBP La stimulates the post-transcriptional expression of TF ZEB1 and mediates TGF-β Induced EMT and stemness of CSCs [117].…”
Section: Mrna Of Tfs In Cscs As a Target For Regulationmentioning
confidence: 99%